Urgent robotic coronary revascularization in a pregnant womanAJOG Global Reports at a Glance - Katie Hawthorne, MD; Maria Eleni Drosou, MD; Thomas A. Shapiro, MD; Serge Sicouri, MD; Eric M. Gnall, MD; Basel Ramlawi, MD; Ozgun Erten, MD; Francis Sutter, MD; Aleksander Dokollari, MD; Gianluca Torregrossa, MD (Elsevier, 2023)
BACKGROUND: Outcomes of robotic-assisted coronary artery bypass grafting in pregnant women have not been assessed. OBJECTIVE: This study aimed to understand the importance of minimally invasive robotic-assisted coronary artery bypass grafting in pregnant woman with coronary artery disease. We describe the case of a G3P1011 woman at 19+6 weeks' gestation presenting with a non-ST myocardial infarction treated with off-pump hybrid robotic-assisted revascularization. STUDY DESIGN: This study describes the surgical approach for a pregnant woman presenting with non-ST myocardial infarction treated with hybrid robotic-assisted revascularization. RESULTS: A coronary angiography demonstrated a culprit lesion of 90% stenosis in the left anterior descending coronary artery and an 80% stenosis in the right coronary artery. Because of the high rate of complications with traditional coronary artery bypass grafting, the heart team opted for hybrid robotic-assisted revascularization and the postoperative recovery was uneventful. CONCLUSION: Robotic coronary artery bypass grafting can be the preferred surgical choice to decrease maternal and fetal mortality in patients undergoing coronary artery bypass grafting, and it is an important tool in the surgical armamentarium.